Epidermal growth factor receptors in the oesophagus. Issue 4 (April 1992) - Jankowski, J; Murphy, S; Coghill, G; Grant, A; Wormsley, K G; Sanders, D S; Kerr, M; Hopwood, D
Abstract : The quantity and distribution of epidermal growth factor receptors (EGF-R) in oesophageal mucosa was studied in the oesophagus in order to determine its role in oesophageal disease. Fifty five biopsies were taken from different levels of the oesophagus in 25 consecutive patients undergoing endoscopy. Another group of eight patients with histologically proven Barrett's oesophagitis had a biopsy taken from the area of columnar lined oesophagus. A peripheral, membranous pattern was seen predominantly confined to the basal and immediately suprabasal cells in all of the first group of patients. In the superficial cells a few granular cytoplasmic structures were positive. All patients with Barrett's oesophagitis showed EGF-R staining of the surface epithelium. A computerised planimeter was used to determine the proportion of stained areas of squamous cells which were expressed as a percentage of the total area of squamous cells. The difference in the area of cells stained for EGF-R between normal and inflamed oesophageal mucosa (29.5% and 43.1% respectively) was significant (p less than 0.001).